A Dimension of Child Emergency: Psychiatric Emergency and Nursing Approach - Bahar Aksoy; İlknur Kahriman (Journal of Pediatric Emergency and Intensive Care Medicine, 2022)

(untitled)
In recent years, there has been a significant increase in applications to pediatric emergency services. Psychiatric emergencies are one of the frequent applications made to pediatric emergency services. Psychiatric emergencies are the first places that children and families will go to, as a situation that applications urgent intervention. However, in cases that do not require emergency intervention, children and families should apply to psychiatry services, while most of the applications are made to emergency services. Psychiatric emergencies constitute 3-12% of the applications made to emergency services. Therefore, in this review, psychiatric emergencies, risk factors, incidence, identification and evaluation of psychiatric emergencies, specific psychiatric emergencies and nursing approach are discussed in this review.